CONCEPTUALIZACIÓN DE LA CALIDAD EN EL SOGC A PARTIR DE LA REFORMA DE LA LEY 100. (2016)
The guaranty of quality it is the issues more frequent in the Institutions of Health, as in the private practice. All the activities of group created to the patient’s receive the major and best outcome and lower risk, at moment of have has a medical attention. The quality assurance is the most important action to the guaranty of quality. In the profesional, work of medicine its necessary guaranty at the patients receiving the best human and technological recourses, available, with a reasonable way. The objective of this article is the define concepts of quality assurance in the SOGC framing them from the law 100.